2012
DOI: 10.1016/j.bcp.2012.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Novel fluorescent antagonist as a molecular probe in A3 adenosine receptor binding assays using flow cytometry

Abstract: The physiological role of the A3 adenosine receptor (AR) was explored in cardiac ischaemia, inflammatory diseases and cancer. We report a new fluorophore-conjugated human (h) A3AR antagonist for application to cell-based assays in ligand discovery and for receptor imaging. Fluorescent pyrazolo[4,3-e][1,2,4]triazolo[1,5-c]pyrimidin-5-ylamine (pyrazolo-triazolo-pyrimidine, PTP) and triazolo[1,5-c]quinazolin-5-yl)amine (triazolo-quinazoline, TQ) AR antagonists were compared. A chain-extended and click-conjugated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 28 publications
1
61
0
Order By: Relevance
“…In such way, a new fluorophore-conjugated A 3 R antagonist ( 16 ) (Table 2) was synthesized and used for cell-based applications. This compound clearly labelled the A 3 R at the plasma membrane of CHO cells expressing the receptor and by means of FCM a very high specific-to-nonspecific binding ratio was obtained (Kozma et al, 2012). Interestingly, by using this last approach an equilibrium binding constant comparable to that calculated from kinetic radioligand experiments in membranes was observed (Kozma et al, 2012).…”
Section: Uncovering the Biology Of G Protein-coupled Purinergic Rementioning
confidence: 99%
See 1 more Smart Citation
“…In such way, a new fluorophore-conjugated A 3 R antagonist ( 16 ) (Table 2) was synthesized and used for cell-based applications. This compound clearly labelled the A 3 R at the plasma membrane of CHO cells expressing the receptor and by means of FCM a very high specific-to-nonspecific binding ratio was obtained (Kozma et al, 2012). Interestingly, by using this last approach an equilibrium binding constant comparable to that calculated from kinetic radioligand experiments in membranes was observed (Kozma et al, 2012).…”
Section: Uncovering the Biology Of G Protein-coupled Purinergic Rementioning
confidence: 99%
“…This compound clearly labelled the A 3 R at the plasma membrane of CHO cells expressing the receptor and by means of FCM a very high specific-to-nonspecific binding ratio was obtained (Kozma et al, 2012). Interestingly, by using this last approach an equilibrium binding constant comparable to that calculated from kinetic radioligand experiments in membranes was observed (Kozma et al, 2012). Another adenosine receptor fluorescent ligand used in FCM was compound 12 (Table 2), which consisted of an Alexa Fluor 488-conjugated A 2A R agonist.…”
Section: Uncovering the Biology Of G Protein-coupled Purinergic Rementioning
confidence: 99%
“…However, the approach has also been used for ligands for adenosine [85, 86], adrenergic [87, 88], cannabinoid [89], chemokine [90, 91], galanin [92], long chain fatty acid [93], neuropeptide Y [94], somatostatin [95, 96], urotensin [97], vasopressin [98]and yeast α-factor [82, 99102] receptors.…”
Section: Fluorescent Ligandsmentioning
confidence: 99%
“…In order to overcome this problem, two differing methods were recently introduced: one on membrane fragments 7 and another on intact cells. 6 Kecskès et al used an Alexa Fluor 488-tagged A 2A AR antagonist MRS5346 ( 53 ) in a newly developed ligand binding assay that uses fluorescence polarization (FP) with A 2A -HEK293 cell membranes. 7,41 The same study also reported a TAMRA derivative MRS5347 ( 55 ) and a BODIPY 650/665-X derivative MRS5418 ( 54 ) synthesized by Kumar et al 41 Conjugates 54 and 55 were designed for FM, and the structure was based on a pyrazolo[4,3- e ][1,2,4]triazolo[1,5- c ]pyrimidine-5-amine (PTP) scaffold that promotes high affinity and selectivity as antagonists for the A 2A AR.…”
Section: Fluorescent Ar Ligands As Tracers In Ligand Binding Assaysmentioning
confidence: 99%
“…6,7 Recently, the expense, health risks, and disposal issues that radioligands pose have increased the need to develop more efficient techniques. Fluorescent methods solve many of these issues associated with radioactivity, in addition to providing other advantages.…”
mentioning
confidence: 99%